Chalcones as Anti-Glioblastoma Stem Cell Agent Alone or as Nanoparticle Formulation Using Carbon Dots as Nanocarrier - Eduardo A. Veliz; Anastasiia Kaplina; Sajini D. Hettiarachchi; Athina L. Yoham; Carolina Matta; Sabrin Safar; Meghana Sankaran; Esther L. Abadi; Emel Kirbas Cilingir; Frederic A. Vallejo; Winston M. Walters; Steven Vanni; et al. (MDPI AG, 2022)
The current prognosis for glioblastoma is dismal. Treatment-resistant glioblastoma stem cells (GSCs) and the failure of most drugs to reach therapeutic levels within the tumor remain formidable obstacles to successful treatment. Chalcones are aromatic ketones demonstrated to reduce malignant properties in cancers including glioblastoma. Nanomedicines can increase drug accumulation and tumor cell death. Carbon-dots are promising nanocarriers that can be easily functionalized with tumor-targeting ligands and anti-cancer drugs. Therefore, we synthesized a series of 4'-amino chalcones with the rationale that the amino group would serve as a "handle" to facilitate covalent attachment to carbon-dots and tested their cytotoxicity toward GSCs. We generated 31 chalcones (22 4'-amino and 9 4' derivatives) including 5 novel chalcones, and found that 13 had an IC50 below 10 µM in all GSC lines. After confirming that the 4-amino group was not part of the active pharmacophore, chalcones were attached to transferrin-conjugated carbon-dots. These conjugates were significantly more cytotoxic than the free chalcones, with the C-dot-transferrin-2,5, dimethoxy chalcone conjugate inducing up to 100-fold more GSC death. Several of the tested chalcones represent promising lead compounds for the development of novel anti-GSC drugs. Furthermore, designing amino chalcones for carbon-dot mediated drug delivery is a rational and effective methodology.